Determination of Sitagliptin Levels in Rats Serum by HPLC and its Pharmacokinetic Investigation in Existence of Sucralose - Dayyih, Wael Abu; Hamad, Mohammed (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
It is an interest of the current work to develop a simple, valid and rapid chromatographic method for the quantification of sitagliptin in rats' serum. Accordingly, the pharmacokinetic parameters of sitagliptin was investigated for any possible interaction between sitagliptin and sucralose. The developed HPLC method was validated for sitagliptin determination in rat’s serum. Results indicated an accomplished overall intra-day precision and accuracy values of 0.139-4.028 (CV%) and 99.48-107.12% respectively. On the other hand, inter-day precision and accuracy results recorded values of 0.150-2.810 (CV%) and 99.90-116.00% respectively. Moreover, the coefficient of correlation was determined at a value of 0.99950 with reasonable sensitivity and selectivity. Effect of sucralose showed strong significant correlation on sitagliptin serum profile. The precise, accurate, linear, sensitive and selective HPLC method will be elaborated in the context of the current work with emphasis on sucralose negative effect on sitagliptin level in rat’s serum. Such finding is a guidance for physicians to reconsider the use of such sweeteners for diabetic patients